2023
DOI: 10.1111/omi.12417
|View full text |Cite
|
Sign up to set email alerts
|

One‐carbon metabolism and microbial pathogenicity

Abstract: One‐carbon metabolism (OCM) pathways are responsible for several functions, producing a number of one‐carbon unit intermediates (formyl, methylene, methenyl, methyl) that are required for the synthesis of various amino acids and other biomolecules such as purines, thymidylate, redox regulators, and, in most microbes, folate. As humans must acquire folate from the diet, folate production is a target for antimicrobials such as sulfonamides. OCM impacts the regulation of microbial virulence such that in a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Studies have shown that methylene groups can increase the lipophilicity of compounds ( Møller, 2020 ), and in addition, methylene groups can act as methylating agents, playing a key role in DNA methylation ( Botezatu et al, 2014 ). Additionally, methylene groups are involved in the synthesis of many amino acids and biologically active molecules as well as in metabolic processes ( Stocke and Lamont, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that methylene groups can increase the lipophilicity of compounds ( Møller, 2020 ), and in addition, methylene groups can act as methylating agents, playing a key role in DNA methylation ( Botezatu et al, 2014 ). Additionally, methylene groups are involved in the synthesis of many amino acids and biologically active molecules as well as in metabolic processes ( Stocke and Lamont, 2023 ).…”
Section: Discussionmentioning
confidence: 99%